RANCANG BANGUNG APLIAKSI BERBASIS ANDROID UNTUK PENCARIAN LOKASI INDEKOS MENGGUNAKAN FRAMEWORK FLUTTER DI KOTA CIREBON - Handreyan Rizki Pratama; Nining Rahaningsih; Fadhil M. Basysyar (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Continue the school to the college level who come from outside the city would need a place lodger, as well as pakerja that comes from outside the region need the same thing. Search place lodger with the use of a manual will require the time of a day. Today many application that provides easy access to help find a place lodger. But of the many applications , sometimes not specific, so a lodger who are found not in accordance with expectations. This study aims to develop an Android-based location search lodger using the framework flutter in the region of Cirebon City, making it easier for the students/workers from outside the city in search of the lodger needed. Feature of this app is a GPS to facilitate the students/workers from outside the city in search of the lodger needed. where this feature is different from the application that has been built before. The method used in developing this application is the waterfall method. The stages are requirements analysis, system design, implementation, integration and testing. The expected outcome of this research is that a of some aspects of the quality of the software aspects of reliability, effeciency, integrity and usability. Keyword : Android, GPS, FLutter